2006
DOI: 10.1111/j.1945-5100.2006.tb00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Asteroid 3628 Božněmcová: Covered with angrite-like basalts?

Abstract: Abstract-A detailed analysis of the reflectance spectrum of asteroid 3628 BoûnÏmcová, previously identified as a possible ordinary chondrite parent body, indicates that its surface consists of an assemblage dominated by clinopyroxene and plagioclase feldspar. The clinopyroxene is Fe 2+ -bearing (likely in the range Fs~1 0-20 ), with >90% of the Fe 2+ being present in the M1 crystallographic site (spectral type A). The clinopyroxene:plagioclase feldspar ratio is between ~2 and 3 (~55-75% clinopyroxene, ~20-33% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…So even though Fe 2+ is concentrated in the M1 site, bands due to the Fe 2+ in the M1 site will not be apparent unless there is little to no discernible Fe 2+ in the M2 site. Cloutis et al (2006) find that Angra dos Reis has a higher percentage of Fe 2+ in the M2 site than D'Orbigny or LEW 86010, which is consistent with the spectral properties of these angrites.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…So even though Fe 2+ is concentrated in the M1 site, bands due to the Fe 2+ in the M1 site will not be apparent unless there is little to no discernible Fe 2+ in the M2 site. Cloutis et al (2006) find that Angra dos Reis has a higher percentage of Fe 2+ in the M2 site than D'Orbigny or LEW 86010, which is consistent with the spectral properties of these angrites.…”
Section: Resultssupporting
confidence: 82%
“…Hardersen et al (2006) has proposed that S-type asteroid 138 Tolosa could possibly be a mixture of Type A and B pyroxenes, but this object does not appear spectrally similar to measured angrites. Cloutis et al (2006) has investigated whether 3628 BoûnÏmcová could be covered with angritic material. Asteroids classified as Sr in the Bus and Binzel (2002b) taxonomy, such as 3819 Robinson (semimajor axis of 2.77 AU), have spectra that match angrites very closely in the visible wavelength region (0.44 to 0.92 µm) (Fig.…”
Section: Asteroidsmentioning
confidence: 99%
“…The only asteroid that provides a good spectral match to the angrites is the km-sized Mars Trojan asteroid (5261) Eureka Trilling et al 2007). The Srclass asteroid 3819 Robinson matches some angrites in the visible region but not in the near-infra-red , and asteroid 3628 Boznemcova´might be an unsampled angrite-like body (Cloutis et al 2006). Both are £10 km in diameter.…”
Section: Introductionmentioning
confidence: 91%
“…The Sr‐ class asteroid 3819 Robinson matches some angrites in the visible region but not in the near‐infra‐red (Burbine et al. 2006), and asteroid 3628 Boznemcová might be an unsampled angrite‐like body (Cloutis et al. 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Abundant plagioclase feldspar has also been identified in O-type asteroid 3628 Božněmcová using VNIR reflectance spectra by Cloutis et al (2006). The spectrum of Božněmcová can be matched by an assemblage of clinopyroxene (~55-75%) and plagioclase feldspar (~20-33%), which would be broadly similar to angrite meteorites (Binzel et al, 2001;Cloutis et al, 2006). They suggested that Božněmcová could have formed by melting and differentiation under oxidizing conditions and probably represents an unsampled angritelike body.…”
Section: Plagioclase On the Asteroidsmentioning
confidence: 98%